The Influence of Online Games towards Students' Learning Interests at Grade X SMK Dara Jingga Star Up Vocational School - Zulkarnain, Zulkarnain; Prasetyo, Dian Estu; Fitry, Alchonity Harika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The purpose of this study was to determine the effect of online games on student interest in learning PJOK lessons at SMK Star Up Dara Jingga. The benefits of this research are to add references to studies related to online game opium and provide input to relevant parties in implementing education, be it schools, teachers, and other researchers. The method used in this research is the Ex-post facto method. The data analysis technique in this research is the product-moment correlation. The population in this study were students of class X SMK Star Up Dara Jingga and the sample in this study were students of class X SMK Star Up Dara Jingga totaling 16 students.Based on the results of the study, it shows that there is a significant influence online games on student learning interest in learning PJOK SMK Star Up Dara Jingga from the data obtained based on the results of hypothesis testing stating that the hypothesis is accepted because the calculated r obtained is 0.8950 while the r table 0.497 with a significant 0.05 so it can be concluded that Ha is accepted.